Análisis socio-económico de los comerciantes de ganado que participan en la feria “Asogan-sd” Cantón Santo Domingo, Provincia de Santo Domingo de los Tsáchilas. - Triana Molina, Karina Estefania (2019)
This research work was carried out at the ASOGAN-SD cattle fair in the Santo Domingo Canton, with the objective of analyzing the socioeconomic situation of the merchants, identifying the places of origin of the cattle, ways of distribution and establishing the loading systems, resources that used in the activity, based on research, one of the most important fairs held in Ecuador is the ASOGAN-SD, as there are several examples of breeds of meat and milk cattle adapted to the humid tropics with more than 300 track animals and three international games, due to the variety of exposed breeds, The project was carried out through data collection, through photographs, field notebook and the application of the questionnaire; then proceed to order and analyze, in order to achieve the results. Livestock merchants state that, although the country's economic situation is not at a good time, they must continue working to generate income for their homes. Regarding the social and economic aspects analyzed Based on the research, it was determined that 84% of the livestock traders have their own capital to work with a value that fluctuates between 2000 and 5000 dollars, also expressed that the gain on days Tuesday ranges from 100 to 300 dollars, 56% consider the activity as good while only 5% consider it excellent, 35% of respondents said they have a problem with late payments, with respect to where they live, the merchants, expressed that it is their own and fully paid cement built, with electricity, drinking water. When identifying the places of origin of the animals, the vast majority that will come from farms and 30% from other fairs such as Carmen Manabí will be identified, being transported mostly in own vehicles, one of the main problems when transporting livestock It is the problem of the animal, it was concluded that the respondents prefer to market the livestock to the eye, this means that they only observe the animals and offer a certain amount of money without knowing how much it weighs. It was determined that the merchants expect from the public institutions a community dispensary, permanent police presence on the days of the fair, and a banking entity within the fair's facilities and request the regulation of informal merchants of different goods and items inside and outside of the fair. Keywords: socioeconomic analysis, livestock traders, livestock fairs